The Impact of Smart-phones Usage on Third-Year Undergraduates in Tanzania: A Case of the University of Dar es Salaam - Mwabungulu, Elias; Mungwabi, Hosea (University of Dar es Salaam Library Journal, 2017)
This study investigated the impact of the use of smart-mobile phone by undergraduate students at the University of Dar es Salaam. Specifically, the study sought to establish the academic-related purposes for which university students use smart-phones and the impact of such usage on their academic life. To achieve these objectives, the study employed a mixed methods research approach in which questionnaires and an interview guide were used to collect data from a sample size of 166 students. The results of the study revealed that the majority of undergraduate students own smart-phones which they used for different purposes, including for academic intentions such as reading lecture materials, and watching academic-related videos. The study findings also reveal that smart-phones to an extent enhance the undergraduate students ' performance of academic activities.